PENGARUH KEMAMPUAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI pada kantor Perumnas Regional II Palembang ( 2019) - Imam Santoso (Sekolah Tinggi Manajemen IMMI Jakarta, 2021)
This research is aimed at obtaining information related to the effect of the work ability, and work motivation on the performance of the employees . Reseach has been implemented using path analysis after all variables put into matrix of correlkation. In this research employees had been chosen as a unit of analysis 70 .The resuld had showed that ( 1) work ability had direct effect on the performance of the employees, (2) work motivation had direct effect on the performance of the employees ( 3 ) work ablity had and indirect effect on the performance of the employees trough work motivation. The resuld suggest that work ability, work motivation are important determinants of the employees performance. Based on those findings it could be concluded that any cange or variation which occurred in the performance employees of Perumnas Regional 2 had been effected by work ability, and work motivation.PENGARUH KEMAMPUAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAIpadakantor Perumnas Regional IIPalembang( 2019)